G protein-coupled estrogen receptor 1 and collagen XVII endodomain expression in human cutaneous melanomas: can they serve as prognostic factors? - Uğur Çakır; Petra Balogh; Anikó Ferenczik; Anikó Ferenczik; Valentin Brodszky; Tibor Krenács; Sarolta Kárpáti; Miklós Sárdy; Péter Holló; Melinda Fábián (Frontiers Media S.A., 2024)
Melanoma incidence is increasing globally. Although novel therapies have improved the survival of primary melanoma patients over the past decade, the overall survival rate for metastatic melanoma remains low. In addition to traditional prognostic factors such as Breslow thickness, ulceration, and mitotic rate, novel genetic and molecular markers have been investigated. In our study, we analyzed the expression of G-protein coupled estrogen receptor 1 (GPER1) and the endodomain of collagen XVII (COL17) in relation to clinicopathological factors in primary cutaneous melanomas with known lymph node status in both sexes, using immunohistochemistry. We found, that GPER1 expression correlated with favorable clinicopathological factors, including lower Breslow thickness, lower mitotic rate and absence of ulceration. In contrast, COL17 expression was associated with poor prognostic features, such as higher tumor thickness, higher mitotic rate, presence of ulceration and presence of regression. Melanomas positive for both GPER1 and COL17 had significantly lower mean Breslow thickness and mitotic rate compared to cases positive for COL17 only. Our data indicate that GPER1 and COL17 proteins may be of potential prognostic value in primary cutaneous melanomas.